The hypothalamic–pituitary–gonadal axis controls muscle stem cell senescence through autophagosome clearance. Issue 1 (27th November 2020) - Kim, Ji‐Hoon; Park, Inkuk; Shin, Hijai R.; Rhee, Joonwoo; Seo, Ji‐Yun; Jo, Young‐Woo; Yoo, Kyusang; Hann, Sang‐Hyeon; Kang, Jong‐Seol; Park, Jieon; Kim, Ye Lynne; Moon, Ju‐Yeon; et al.
Abstract: Background: With organismal aging, the hypothalamic–pituitary–gonadal (HPG) activity gradually decreases, resulting in the systemic functional declines of the target tissues including skeletal muscles. Although the HPG axis plays an important role in health span, how the HPG axis systemically prevents functional aging is largely unknown. Methods: We generated muscle stem cell (MuSC)‐specific androgen receptor (Ar) and oestrogen receptor 2 (Esr2) double knockout (dKO) mice and pharmacologically inhibited (Antide) the HPG axis to mimic decreased serum levels of sex steroid hormones in aged mice. After short‐term and long‐term sex hormone signalling ablation, the MuSCs were functionally analysed, and their aging phenotypes were compared with those of geriatric mice (30‐month‐old). To investigate pathways associated with sex hormone signalling disruption, RNA sequencing and bioinformatic analyses were performed. Results: Disrupting the HPG axis results in impaired muscle regeneration [wild‐type (WT) vs. dKO, P < 0.0001; Veh vs. Antide, P = 0.004]. The expression of DNA damage marker (in WT = 7.0 ± 1.6%, dKO = 32.5 ± 2.6%, P < 0.01; in Veh = 13.4 ± 4.5%, Antide = 29.7 ± 5.5%, P = 0.028) and senescence‐associated β‐galactosidase activity (in WT = 3.8 ± 1.2%, dKO = 10.3 ± 1.6%, P < 0.01; in Veh = 2.1 ± 0.4%, Antide = 9.6 ± 0.8%, P = 0.005), as well as the expression levels of senescence‐associated genes, p16 Ink4a and p21 Cip1, was significantly increased in the MuSCs, indicating that genetic and pharmacological inhibition of the HPG axis recapitulates the progressive aging process of MuSCs. Mechanistically, the ablation of sex hormone signalling reduced the expression of transcription factor EB (Tfeb) and Tfeb target gene in MuSCs, suggesting that sex hormones directly induce the expression of Tfeb, a master regulator of the autophagy–lysosome pathway, and consequently autophagosome clearance. Transduction of the Tfeb in naturally aged MuSCs increased muscle mass [control geriatric MuSC transplanted tibialis anterior (TA) muscle = 34.3 ± 2.9 mg, Tfeb‐transducing geriatric MuSC transplanted TA muscle = 44.7 ± 6.7 mg, P = 0.015] and regenerating myofibre size [eMyHC + tdTomato + myofibre cross‐section area (CSA) in control vs. Tfeb, P = 0.002] after muscle injury. Conclusions: Our data show that the HPG axis systemically controls autophagosome clearance in MuSCs through Tfeb and prevents MuSCs from senescence, suggesting that sustained HPG activity throughout life regulates autophagosome clearance to maintain the quiescence of MuSCs by preventing senescence until advanced age.